The Effects of Physical Activity on Adverse Side Effects in Chemotherapy Patients - Long-Pero, Maddisen (Office of Student Research and Creative Activity, 2018)
Each year, more than 14 million people worldwide are diagnosed with cancer. Despite advancements in medicine, a cure for this disease has not been found. Chemotherapy, a common cancer treatment, is often used in an attempt to slow the progression of cancer and achieve remission, but it is also associated with several adverse reactions. Fatigue and reduced cognitive function are notable side effects that can decrease the quality of life for many patients and affect their ability to function as they did prior to the diagnosis. In the past, individuals treated for chronic illnesses were often told by their physicians to rest as much as possible and avoid physical activity to preserve their strength. However, current research suggests that exercise can mitigate many chemotherapy side effects. Adhering to the guidelines put forth by the American College of Sports Medicine in Exercise Management for Persons with Chronic Diseases and Disabilities (CDD4), individuals undergoing chemotherapy can and should participate in a regular exercise regime to avoid chemotoxicity, thus improving overall health. As cancer rates are expected to increase in the coming decades, physical activity should be integrated into the typical medication-based care plans of cancer patients to yield additional health benefits.
Keywords: Cancer--Chemotherapy; Cancer--Exercise therapy